Women's Alternative Media: Agents of Change on the Issue of Women's Roles in Indonesia - Amelia, Diah; Amanah, Siti; Muljono, Pudji; Hapsari, Dwi Retno (Informasi, 2024)
ABSTRACTProgress in achieving gender equality and empowering women in Indonesia has been too slow and fragmented. The media can provide a voice and a platform for placing women's role issues on the development agenda. As in the education, health, economic, labor, and political sectors. However, in reality, there is a significant gender gap in mainstream media companies so that women are not represented optimally and steps to improve gender equality are limited. Alternative media is very possible to take a role in explaining issues of gender equality and women's empowerment. Because this type of media can connect various sectors, including trade unions, social movements, organizations and various elements of society. Researchers use the concept of gender and communication development, Standpoint theory, and alternative media. The approach used in this study is literature review research methodology. The results of this study explain that journalists in alternative media consider gender awareness and sensitivity important in themselves to be able to protect and defend women's interests. In fact, alternative media provide wide opportunities for journalists to raise strategic issues of equality and women's empowerment. Keywords: Alternative, Empowerment, Journalists, Media, Women